Implementing Energy Subsidy Reforms : An Overview of the Key Issues - Vagliasindi, Maria (World Bank, Washington, DC, 2012)
Poorly implemented energy subsidies are economically costly to taxpayers and damage the environment. This report describes the emerging lessons that could help policy makers to address implementation challenges, including overcoming political economy and affordability constraints. The analysis provides strong evidence of the success of reforms in reducing the associated fiscal burden. For the selected sample of 20 developing countries, the average energy subsidy recorded in the budget was reduced from 1.8 percent in 2004 to 1.3 percent of gross domestic product in 2010. The reduction of subsidies is particularly remarkable for net energy importers. In spite of the relatively price inelastic demand for gasoline and diesel, fossil fuel consumption in the road sector (per unit of gross domestic product) declined in the 20 countries examined from 53 (44) in 2002 to about 23 kilotonnes oil equivalent per million of gross domestic product in 2008 in the case of gasoline (diesel). The most notable decline in consumption was recorded in the low-income and lower-middle-income countries. This reflects the much higher rate of growth in gross domestic product in this group of countries. And it underlines the opportunities to influence future consumption behavior rather than modifying the existing consumption patterns, overcoming inertia and vested interests. Similar trends are recorded for power consumption. While there is no one-size-fits-all model for subsidy reform, implementation of compensatory social policies and an effective communication strategy, before the changes were introduced, made a difference in securing the successful implementation of reforms.